L'approche par « compétences » dans l'enseignement professionnel français - Josiane Paddeu; Patrick Veneau
This article demonstrates teachers' work of resistance in response to the imposition of a competence-based approach. We first highlight the specific notion of competence as it is built into the evaluatory rubric for a vocational diploma (and more generally into the whole of vocational education) in France. Then, in a section on practical exams, we examine the way teachers evaluate diploma candidates and particularly the reference points they use in their evaluations, which are quite different from the reference points built into the official rubric. In fact, the instructors attach more importance to the processes, the methods, and the kinds of reasoning used or put into practice by the candidates than to the results or performances listed in the rubric. Finally, a section dedicated to the evaluation of PFMP (workplace internships) demonstrates how evaluating « competences » in those contexts makes little sense.